Epidemiology of cardiomyopathies and incident heart failure in a population-based cohort study. Issue 17 (30th December 2021) - Brownrigg, Jack RW; Leo, Vincenzo; Rose, Joel; Low, Eric; Richards, Sarah; Carr-White, Gerry; Elliott, Perry M
Abstract : Aims: The population prevalence of cardiomyopathies and the natural history of symptomatic heart failure (HF) and arrhythmia across cardiomyopathy phenotypes is poorly understood. Study aims were to estimate the population-diagnosed prevalence of cardiomyopathies and describe the temporal relationship between a diagnosis of cardiomyopathy with HF and arrhythmia. Methods: People with cardiomyopathy (n=4116) were identified from linked electronic health records ( 9 million individuals; 2000–2018) and categorised into hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM), arrhythmogenic right ventricular cardiomyopathy (ARVC), restrictive cardiomyopathy (RCM) and cardiac amyloidosis (CA). Cardiomyopathy point prevalence, rates of symptomatic HF and arrhythmia and timing relative to a diagnosis of cardiomyopathy were determined. Results: In 2018, DCM was the most common cardiomyopathy. DCM and HCM were twice as common among men, with the reverse trend for ARVC. Between 2010 and 2018, prevalence increased for ARVC by 180% and HCM by 9%. At diagnosis, more patients with CA (66%), DCM (56%) and RCM (62%) had pre-existing HF compared with ARVC (29%) and HCM (27%). Among those free of HF at diagnosis of cardiomyopathy, annualised HF incidence was greatest in CA and DCM. Diagnoses of all cardiomyopathies clustered around the time of HF onset. Conclusions: The recorded prevalence of all cardiomyopathies increased over the past decade. Recognition of CA is generally preceded by HF, whereas individuals with ARVC or HCM more often developed HF after their cardiomyopathy diagnosis suggesting a more indolent course or better asymptomatic recognition. The clustering of HF and cardiomyopathy diagnoses suggests opportunities for presymptomatic or earlier diagnosis.